Extrahepatic manifestations in chronic hepatitis C virus carriers. (April 2015) - Rosenthal, E; Cacoub, P
Patients with chronic hepatitis C virus (HCV) infection frequently present with extrahepatic manifestations covering a large spectrum, involving different organ systems leading to the concept of systemic HCV infection. These manifestations include autoimmune phenomena and frank autoimmune and/or rheumatic diseases and may dominate the course of chronic HCV infection. Chronic HCV infection causes liver inflammation affecting the development of hepatic diseases. HCV is also a lymphotropic virus that triggers B cells and promotes favorable conditions for B lymphocyte proliferation, including mixed cryoglobulinemia (MC) and MC vasculitis, which is the most prominent extrahepatic manifestation of chronic HCV infection. HCV may also promote a low-grade chronic systemic inflammation that may affect the development of some extrahepatic manifestations, particularly cardiovascular and cerebral vascular diseases. Recognition of extrahepatic symptoms of HCV infection could facilitate early diagnosis and treatment. The development of direct-acting antiviral agents (DDAs) has revolutionized HCV treatment. DDAs, as well as new B-cell-depleting or B-cell-modulating monoclonal antibodies, will expand the panorama of treatment options for HCV-related extrahepatic manifestations including cryoglobulinemic vasculitis. In this context, a proactive, integrated approach to HCV therapy should maximize the benefits of HCV therapy, even when liver disease is mild.